(untitled) (Global Journal of Human-Social Science, 2023)
The PYLA Vocational Test is an illustrative questionnaire that seeks to inquire about vocational aptitudes and interests from a comprehensive approach with a series of strategically and intentionally selected images color psychology This includes specific generic and hierarchical competencies characteristic of the personality and a profile by professional area